A study of tension fabric membrane structures under in-plane loading: Nonlinear finite element analysis and validation. (15th September 2015) - Dinh, T.D.; Rezaei, A.; Puystiens, S.; Van Craenenbroeck, M.; Carbonez, K.; De Laet, L.; Mollaert, M.; Van Hemelrijck, D.; Van Paepegem, W.
Abstract: Analysis of tension fabric structures exhibits severe nonlinearities because of the large deformation of the fabric membrane and its peculiar material behavior. At this moment, there is limited literature on analysis and design of this kind of structures. A realistic numerical simulation can serve as a driving force in the development of these structures. This article presents a nonlinear finite element analysis of a tension fabric membrane structure used in foldable architectural applications. Geometrical and material nonlinearities are considered in the finite element model which is implemented in the ABAQUS/standard software. The numerical results are validated with the experimental data obtained from digital image correlation (DIC) technique. Good agreement between the simulation and the experiments is achieved. Moreover, the case study considered in this work can be used as a benchmark for numerical simulations in the research field.